Bulgarian-Style Fаct-Checking – Do We Need Ministry of Truth? - Simeonova, Lora (Media and Language, 2017)
Fighting fake news and finding a cure against disinformation and propaganda was one of the trending topics in 2017. The “True/False” project, an experimental fact-checking platform, was created to answer the question: “How are fake news shaping Bulgarian media landscape?”. This study reveals the results of the 6 months-long monitoring of the Bulgarian sites for sensations and manipulations and analyses whether fact-checking platforms are effective against disinformation on the Internet.
Keywords: fact-checking; fake news; click-byte; propaganda; opinion makers; social networks; echo chambers